ANALISIS CIRCULAR MODEL OF SOME AKUN INSTAGRAM KLIEN @SALIRAMART CV TALAGASALIRA INDOTRADING DI TOS CREATIVE AGENCY - Hilyati, Siti Itsnaeni; David Rizar Nugroho; Ika Yuliasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the application of the Circular Model of SOME on the Instagram account of client @saliramart at TOS Creative Agency. The method used is descriptive qualitative. Primary data was collected through interviews, active participation, observation, and documentation, while secondary data was obtained from literature studies. The results of the study show that the Circular Model ofSOME on the @saliramart account was systematically applied by TOS Creativethrough structured content planning, evaluation of engagement and reach metrics, and team management through Trello and WhatsApp. Challenges in the engage stage, due to changes in audience behavior, were overcome with polls, Q&A, and reposts. The implementation of SOME improved brand consistency, publication effectiveness, awareness, sales, and the image of Salira Mart as a local retailer that is friendly and close to its audience.